Prioritas Solusi Permasalahan Pengelolaan Zakat di Propinsi Banten dan Kalimantan Selatan dengan Metode AHP - Nurul Huda; Desti Anggraini; Khalifah Muhamad Ali; Yosi Mardoni; Nova Rini (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Priority Problems and Solutions of Zakah Management in Banten and South Borneo Using AHP. The aim of this study is to map the priority problems and solutions in the management of zakat by using AHP (Analytic Hierarchy Process). Results of a study reveals that there are three kinds of priority issues and solutions zakat management divided by stakeholder agencies (stakeholders) zakat, i.e regulators, zakat organization (OPZ), muzaki and mustahik . The Analytical Hierarchy Process (AHP) model at Banten and Jakarta give a same priority score, i.e. the institution for solving problem in zakat management is OPS dan regulator solution priority is amil sertification  DOI:10.15408/aiq.v6i2.1232